2004
DOI: 10.1136/bjo.2003.036285
|View full text |Cite
|
Sign up to set email alerts
|

Post-brachytherapy initial tumour regression rate correlates with metastatic spread in posterior uveal melanoma

Abstract: Aim: To confirm the prognostic value of post-brachytherapy initial tumour regression rate in posterior uveal melanoma. Methods: A prospective, comparative, observational cohort study was carried out on 147 eyes (147 patients) with choroidal melanoma (mean age 61 years) treated with Ru-106 brachytherapy. Observation procedure: Patients were followed clinically and ultrasonically every 6.7 (SD 0.3) months (1001 examinations). On average each patient was examined 5.8 times (mean follow up 9.6 (3.7) years). The ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
2
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
2
33
2
14
Order By: Relevance
“…It is well known from clinical studies that patients whose tumors respond immediately and rapidly to brachytherapy are significantly more likely to die of metastatic melanoma than patients whose tumors respond much more slowly. 55 Therefore, relative successes in treating planktonic malignancies such as the leukemias compared with solid malignancies may be related in part to the generation of vasculogenic mimicry patterns now documented 3 in a wide variety of solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known from clinical studies that patients whose tumors respond immediately and rapidly to brachytherapy are significantly more likely to die of metastatic melanoma than patients whose tumors respond much more slowly. 55 Therefore, relative successes in treating planktonic malignancies such as the leukemias compared with solid malignancies may be related in part to the generation of vasculogenic mimicry patterns now documented 3 in a wide variety of solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Kaiserman et al 2 reported a correlation between metastatic death and tumour regression after ruthenium-106 plaque radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that a higher rate of regression following radiation therapy in uveal melanoma correlated with an increased risk of metastasis [8,9,10]. With the advent of genetic testing, monosomy 3 and gene expression profiling are now considered as more reliable prognostic indicator for metastatic potential in uveal melanoma [11,12,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of regression of the uveal melanoma following brachytherapy as a prognostic factor for metastasis has been an issue of great interest and debate. Rapid regression of uveal melanoma following brachytherapy has been reported as an independent risk factor for metastasis [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%